ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH KABUPATEN BANJAR NEGARA (Studi Deskriptif Pada Kabupaten Banjarnegara-Jawa Tengah) - Bambang Jatmiko; Ilham Gilar Wicaksono (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
The purpose of this study is to test and prove empirically the existence of correlations between variables of regional taxes, population, economic growth and regional expenditure. The problem in regional revenue (PAD) in Banjarnegara District which is not in accordance with the target set even the income is less than the target set in the previous year. The subject of this study is the Regional Financial and Asset Revenue Management Agency (BPPKAD) of Kabupaten Banjarnegara with an object of financial statements containing regional income, regional expenditure, regional tax, and gross regional domestic income (GRDP). In addition, researchers also use data on the number of population included in the productive age category, the data obtained through the official web of the Central Statistics Agency (BPS) of Banjarnegara Regency. This study uses qualitative methods with secondary data retrieval. Sampling in this study using purposive sampling. The analiss method used in this research is descriptive study. The application to process data in this study uses SPSS v.15.0. The research model used is multiple correlation, where the test aims to find correlations or relationships between two or more variables. Furthermore, the researchers also used the value for money (VFM) method to analyze the PAD owned by the Banjarnegara Regency government. The value for money method has three criteria, namely, efficient, effective and economical (3E).